Cognitive Failure in Adults with Spinal Cord Injury: A Valuable Adjunct Measure for Enhancing Cognitive Assessment and Rehabilitation Outcomes - Ilaria Pozzato; Mohit Arora; Candice McBain; Nirupama Wijesuriya; Yvonne Tran; James W. Middleton; Ashley R. Craig (Neurology International, 2023)
Cognitive impairment is common in persons with spinal cord injury (SCI), impacting their daily functioning and rehabilitation. This study assesses the extent of self-reported cognitive failures in everyday life in persons with SCI and its relationships with objective neurocognitive measures and psychosocial factors, including depressive mood, anxiety, perceived control, and fatigue. The differences between forty-one adults with a chronic SCI and forty-one able-bodied controls were examined. The participants completed the Cognitive Failures Questionnaire (CFQ) to assess cognitive failure and neurocognitive tests assessing attention and executive functions, as well as a psychosocial assessment. The SCI group reported higher cognitive failure rates than the able-bodied group (31.7% versus 19%, p > 0.05). Objective neurocognitive tests did not significantly correlate with the CFQ scores in either group. However, the CFQ scores were positively associated with most psychosocial factors, even after controlling for covariates. The CFQ scores were significantly associated with depressive mood in persons with SCI. These findings highlight the importance of incorporating self-reported cognitive measures into neurocognitive assessments and rehabilitation planning for adults with SCI. Self-reports capture everyday cognitive challenges that objective tests may miss. Additionally, this study highlights the strong connections between cognitive failures and psychosocial issues, particularly mood disorders, emphasizing the need for comprehensive rehabilitation and psychosocial support post-SCI, addressing both cognitive and emotional wellbeing.